Same Faces, Different Labels: Generating the Cross-Race Effect in Face Memory with Social Category Information - Hourihan, Kathleen L. (2013)
Recognition of own-race faces is superior to recognition of other-race faces. In the present experiments, we explore the role of top-down social information in the encoding and recognition of racially ambiguous faces. Hispanic and African-American participants studied and were tested on computer-generated, ambiguous-race faces (composed of 50% Hispanic and 50% African-American features; MacLin & Malpass, 2001). In Experiment 1, faces were randomly assigned to two study blocks. In each block, a group label was provided that indicated that those faces belonged to African-American or to Hispanic individuals. Both participant groups exhibited superior memory for faces studied in the block with the own-race label. In Experiment 2, faces were studied in a single block with no labels, but tested in two blocks in which labels were provided. Recognition performance was not influenced by the labeled race at test. Taken together, these results confirm the claim that purely top-down information can yield the well documented cross-race effect in recognition, and additionally suggest that the bias takes place at encoding rather than testing.